Aetiology and risk factors for head and neck cancer: United Kingdom National Multidisciplinary Guidelines. (May 2016) - Shaw, R; Beasley, N
Abstract: This is the official guideline endorsed by the specialty associations involved in the care of head and neck cancer patients in the UK. It discusses the aetiology and risk factors for head and neck cancer and the recommended interventions appropriate for each risk factor. Recommendations: Recent evidence synthesis from National Institute for Health and Care Excellence suggests that the following brief interventions for smoking cessation work should be used: ○ Ask smokers how interested they are in quitting (R) ○ If they want to stop, refer them to an intensive support service such as National Health Service Stop Smoking Services (R) ○ If they are unwilling or unable to accept a referral, offer a stop smoking aid, e.g. pharmacotherapy. (R) Brief interventions are effective for hazardous and harmful drinking. (R) Specialist interventions are effective in people with alcohol dependence. (R) Most people with alcohol dependence can undergo medically assisted withdrawal safely at home, after risk assessment. (R) Management of leukoplakia is not informed by high-level evidence but consensus supports targeted use of biopsy and histopathological assessment. (R) The management of biopsy proven dysplastic lesions favours: ○ advice to reduce known environmental carcinogens such as tobacco and alcohol (R) ○ surgical excision when the size of the lesions and the patient's function allows (R) ○ long-term surveillance. (R) Fanconi anaemia patients should: ○ be followed up in a multidisciplinary specialist Fanconi anaemia clinic (G) ○ have quarterly screening for head and neck squamous cell carcinoma and an aggressive biopsy policy (G) ○ receive prophylactic vaccination against high risk human papilloma virus (G) ○ receive treatment for head and neck squamous cell carcinoma with surgery alone where possible. (G)